Representasi Kesenjangan Sosial dalam Film Parasite - Ismandianto; Feggy Eugueyne Wulan Sari (LPPM Stikosa - AWS, 2021)
Societal gap is a phenomenon that exists between the layers of society which creates mass significant differences between it. Through the movie Parasite, Bong Joon Ho successfully portrayed a visualization of the societal disparity issue that happens between two South Korea families with different economic backgrounds. This research’s sole purpose is to analyze and evaluate the representation of societal gap which is depicted thoroughly in Parasite’s filmography. This research uses the method of qualitative research with John Fiske’s semiotic analysis. The subject is the movie Parasite which is directed by Bong Joon Ho. The data is obtained by the method of observing and documentation. The data’s unit of analysis is picked solely by the scenes that interpret signs of societal gap, which rounds up to 31 scenes. The data’s examination technique uses the technique of source’s triangulation. The research has brought up a few results such as, (1) The reality level and societal gap is represented in aspects of appearance, the way each families speak, behavior, movements, expression, and the environment that they reside at. (2) The level of representation and societal disparity is illustrated through aspects of the film such as, camera, lighting, music, and voices. (3) The level of ideology and portrayals of societal gap values can be assured to contain values of socialists and capitalists. In the aspect of socialists, the societal gap is seen as something that stands out because of the significant differences that exist between the different layers of society. Meanwhile, the capitalist values can be seen in how the movie has portrayed how a person with a higher position in the society is the capital holder and the ones that exist in the middle to the lower class of society depends themselves on the ones that resides on the higher class of society.